2020
DOI: 10.3390/cells9020298
|View full text |Cite
|
Sign up to set email alerts
|

A-Kinase Anchoring Protein 1: Emerging Roles in Regulating Mitochondrial Form and Function in Health and Disease

Abstract: Best known as the powerhouse of the cell, mitochondria have many other important functions such as buffering intracellular calcium and reactive oxygen species levels, initiating apoptosis and supporting cell proliferation and survival. Mitochondria are also dynamic organelles that are constantly undergoing fission and fusion to meet specific functional needs. These processes and functions are regulated by intracellular signaling at the mitochondria. A-kinase anchoring protein 1 (AKAP1) is a scaffold protein th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 72 publications
(104 reference statements)
0
29
0
Order By: Relevance
“…In addition, AKAP1 is involved in neuronal development [ 101 ], as demonstrated by experiments in cultured hippocampal neurons, where increasing AKAP1 levels increased dendritic outgrowth and reduced the number of synapses [ 102 ]. AKAP1 tethers at the OMM both PKA and the opposing phosphatases PP1 and Calcineurin (CaN) [ 103 ], coordinating mitochondrial fission/fusion through the regulation of the Drp1 phosphorylation extent. Specifically, PKA-dependent phosphorylation of Ser637 inhibits Drp1 and prevents fission, which results in elongated mitochondria [ 78 , 104 ].…”
Section: Key Playersmentioning
confidence: 99%
“…In addition, AKAP1 is involved in neuronal development [ 101 ], as demonstrated by experiments in cultured hippocampal neurons, where increasing AKAP1 levels increased dendritic outgrowth and reduced the number of synapses [ 102 ]. AKAP1 tethers at the OMM both PKA and the opposing phosphatases PP1 and Calcineurin (CaN) [ 103 ], coordinating mitochondrial fission/fusion through the regulation of the Drp1 phosphorylation extent. Specifically, PKA-dependent phosphorylation of Ser637 inhibits Drp1 and prevents fission, which results in elongated mitochondria [ 78 , 104 ].…”
Section: Key Playersmentioning
confidence: 99%
“…[ 8 ] The mitochondria‐localized AKAP1 tethers PKA to the cytosolic surface of the outer mitochondrial membrane (OMM) in close proximity of local targets to maintain the mitochondrial function. [ 9 ] A previous study has reported that AKAP1 expression is significantly downregulated in adipose tissues of obese subjects when comparing with lean subjects. [ 10 ] Moreover, other studies have revealed the phenomenon that disruption of PKA regulatory subunit in mice leads to a lean phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…4A ). Recently, the unique involvement of AKAP1 in tumor growth has been reviewed ( 14 ). In the present study, the luciferase assay results demonstrated that miR-199a-5p inhibited the activity of the reporter with wild-type 3′UTR of AKAP1 mRNA, but was not able to change the activity of the reporter when the miR-199a-5p binding site was mutated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A-kinase anchoring protein 1 (AKAP1) is a scaffold protein, which recruits protein kinase A, other signaling proteins and RNA to the outer mitochondrial membrane ( 14 ). In hepatocellular carcinoma, high expression levels of AKAP1 are associated with a poor prognosis, suggesting that AKAP1 may serve as a biomarker ( 15 ).…”
Section: Introductionmentioning
confidence: 99%